Akuntabilitas Dana Desa dan Tingkat Partisipasi Masyarakat Terhadap Peningkatan Pembangunan Infrastruktur Desa - Umi Nurhanipah; Ruly Priantilianingtiasari (IPM2KPE, 2023)
This study aims to determine the effect of village fund accountability and the level of community participation on village infrastructure development (Study in Bangoan Village, Kedungwaru District, Tulungagung District). The method used in this study uses a quantitative method by obtaining primary data through a questionnaire form. The population of this research is the village apparatus and the local community in Bangoan Village, Kedungwaru District, Tulungagung Regency. In this study using a sample of 98 respondents. Data analysis used multiple linear regression with data testing in this study using SPSS version 26. The results showed that village fund accountability variables and community participation levels partially affected village infrastructure development variables. Simultaneously, the accountability of village funds and the level of community participation influence village infrastructure development. Keywords: Accountability, Infrastructure Development, Participation Level